Utilization of Museum Collections as Media for Learning History at Ma Al-KhairatBatusuyaGo'o - Moh Rahmat Fauzi Hamka; Misnah; Nuraedah; Juraid Abdul Latief (Kirana Publisher (KNPub), 2023)
This research aims to determine the use of museums as learning resources, learning media, and the role of historical teachers in introducing museum collections as historical learning media. This research applied a qualitative descriptive research design through several stages of data collection techniques, which are observations, interviews and documentation. The results of this research indicated that the use of museums as a history of learning media had been going well. Visiting museums provide new insights and knowledge to students so that students are more active and their interest in learning about local history is higher. However, the implementation had not been optimal and there were still some obstacles generally experienced by teachers who were the unavailability of a specific time given regarding visiting museums, and the difficulty of coordinating students when visiting the UPT Cultural Park and Museum. There are also some obstacles experienced by students which are incomplete information and explanations from several collections stored at UPT Cultural Park and Museum so that students find it difficult to understand what they observe. In other words, museums as learning media in history subjects can increase student enthusiasm for learning because visiting museums provides new insights and knowledge to students so that students are more active, interested, and motivated to learn about local history even though there were several obstacles faced by both students and teachers.